2009
DOI: 10.1258/la.2008.008020
|View full text |Cite
|
Sign up to set email alerts
|

Reported analgesic and anaesthetic administration to rodents undergoing experimental surgical procedures

Abstract: A structured literature review was carried out to assess recent trends in the administration of analgesics and anaesthetics to laboratory rats and mice undergoing surgical procedures. The ScienceDirect database was used to systematically identify studies published in peer-reviewed journals over two periods (2000-2001 and 2005-2006), 86 studies from each time period were included in the review. The total number of animals that underwent surgery, species used, type of procedure, anaesthetic regimen and analgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(148 citation statements)
references
References 12 publications
3
143
0
2
Order By: Relevance
“…In addition to animal welfare, pain must be minimized to avoid confounding experimental outcomes (Chi, 2015). Spontaneous pain is the most common complication after surgery (Stokes, 2009). Furthermore, we found that the minimum dosage of 25 mg/b.w is not enough to alleviate pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to animal welfare, pain must be minimized to avoid confounding experimental outcomes (Chi, 2015). Spontaneous pain is the most common complication after surgery (Stokes, 2009). Furthermore, we found that the minimum dosage of 25 mg/b.w is not enough to alleviate pain.…”
Section: Resultsmentioning
confidence: 99%
“…However, each year, millions of rats undergo surgery for research purposes, but only 20% of researches worldwide reported the administration of analgesics after surgery. The treatment of pain itself varies , drug and dosage varies from institution to institution without a scientific assessment of the analgesic efficiency (Stokes, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…12 Group sizes for rodent studies tend to be larger than studies involving use of larger laboratory species, and rodents are likely to be housed in groups, adding to the challenge of assessing individual animals; the median 'study' size for 'large' laboratory species was 15 compared to 40 for laboratory rodents in papers published during the same period. 1 Similarly, some of the cages used for rodents (including opaque and individually ventilated cages) and cage furnishings (including shelters and nesting materials) may provide barriers to observing the animals. 12 Finally, since rats and mice are nocturnal, pain-associated behaviours may be more obvious in the hours when staffing levels are lowest.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of administration of analgesic agents to animals undergoing surgical procedures is against the refinement used to alleviate pain (Coulter C.A. et al, 2011, Stokes E.L. et al, 2009). …”
Section: Introductionmentioning
confidence: 99%